Performance Evaluation of A/O Membrane Bioreactor System in the Effective Removal of Endocrine-Disrupting Chemicals: the Effect of SRT and Flux Rate - Sozudogru, Onur; Kocoglu, Elif Seda; Yilmaz, Alper Erdem; Bakirdere, Sezgin; Komesli, Okan Tank (SPRINGER INT PUBL AG, 2022)
The effect of SRT and flux rate on the removal of endocrine-disrupting chemicals (EDCs), which have serious adverse effects on human and wildlife endocrine systems, by the laboratory scale submerged flat-sheet anoxic/oxic MBR system (A/O MBR), was investigated. The A/O MBR system was operated for four different sludge holding times (SRT: 10 days, 15 days, 25 days, and 30 days) and three different fluxes' (13 L/m(2).h, 18 L/m(2).h, and 26 L/m(2).h) removal of EDCs (carbamazepine, bisphenol A, methylparaben, ethylparaben, 17 alpha-ethinylestradiol, beta-estradiol, estrone, tonalide, galaxolide, and triclosan) was investigated. The A/O MBR system ensures higher removal of all EDCs (>86%) except for carbamazepine (34%) at high SRT (30d) and low flux (13 L/m(2).h). SRT and flux rate could be vital operating parameters for the removal of carbamazepine, ethylparaben, triclosan, and 17 alpha-ethinylestradiol; however, there might not be a significant effect on the removal of bisphenol A (> 90%), methylparaben (> 91), beta-estradiol (> 99%), estrone (> 99%), tonalide (> 99%), and galaxolide (> 99%). The removal of ethylparaben, 17 alpha-ethinylestradiol, triclosan, and carbamazepine with A/O MBR at high sludge age (30 day) and low flux (13 L/m(2).h) were 93.3%, 96.9%, 86.9%, and 34.8%, respectively. When the SRT was reduced to 10 days, and the flux was increased to 26 L/m(2).h, the removal efficiency of ethylparaben, 17 alpha-ethinylestradiol, triclosan, and carbamazepine decreased to 72.7%, 77.2%, 52.4%, and 1.06%, respectively. It found that SRT and flux rate could be vital parameters for the removal of carbamazepine, ethylparaben, triclosan, and 17 alpha-ethinylestradiol; however, there might not be a significant effect on the removal of bisphenol A, methylparaben, beta-estradiol, estrone, tonalide, and galaxolide.
Keywords: Endocrine-disrupting chemicals; Anoxic/oxic membrane bioreactor; Flux; Sludge retention time; PERSONAL CARE PRODUCTS; DOMESTIC WASTE-WATER; BISPHENOL-A; EMERGING CONTAMINANTS; MASS-SPECTROMETRY; TREATMENT PLANTS; RETENTION TIME; TRACE LEVELS; BY-PRODUCTS; FATE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources